Current practice of venous thromboembolism prevention in acute trusts: a qualitative study. Issue 6 (17th June 2014) - McFarland, L; Murray, E; Harrison, S; Heneghan, C; Ward, A; Fitzmaurice, D; Greenfield, S
Abstract : Objective: To explore the current practice of venous thromboembolism (VTE) prevention in acute trusts. Design: A qualitative research design was used to explore the perceived current practice of thromboprophylaxis, and knowledge and experience of VTE prevention. Data were collected via interviews with personnel from acute trusts and other relevant organisations and charities. Constant comparison was used to generate themes grounded in the data. Setting: The UK. Participants: 17 participants, sampled due to their expertise and knowledge in the field of VTE, were interviewed for the study. Results: No one felt directly responsible for VTE risk assessment and treatment in acute trusts. There were concerns whether any action takes place based on the risk assessment. Low levels of VTE knowledge existed throughout the system. Conclusions: Our study highlights the importance of continuous training to prevent VTE risk assessment being considered a tick box exercise and for clinicians to understand the significance of the procedure to ensure that VTE preventative measures are administered. It is essential that acute trust staff acknowledge that VTE prevention is the responsibility of everyone involved in a patient's care. Concerns remain around prophylaxis treatment, administration and contraindications.